Environmentally friendly synthesis of silicon dioxide nanoparticles and their application for the removal of emerging contaminants in aqueous media. Issue 1 (1st April 2022) - Tejedor, Jennifer; Guerrero, Victor H.; Vizuete, Karla; Debut, Alexis
Abstract: The highly detrimental potential effects that emerging contaminants have for the environment and human health demand the development of sustainable technologies to eliminate these pollutants. In this work, an eco-friendly approach was followed to synthesize S1O2 nanoparticles to be used to remove caffeine and triclosan from synthetic waters. Rice husk was the precursor used, which was subjected to acid leaching treatments using acetic and oxalic acids, and pyrolysis for 2 h at 700 °C. The resulting powders were characterized by X-ray diffraction, Raman and infrared spectroscopies, the Brunauer-Emmett-Teller method, and scanning and transmission electron microscopy. The particles synthesized were amorphous, had an average size between 4.6 and 9.6 nm, and specific surface areas between 208 and 223 m 2 /g. The adsorptive performance of the nanosilica obtained using acetic acid was studied by batch tests. The optimum dosage, maximum removal efficiencies and maximum adsorption capacities were 8 g/L, 76%, and 2.74 mg/g, and 24 g/L, 48%, and 0.75 mg/g for triclosan and caffeine, respectively. The data collected fitted the Sips isotherm model, and the pseudo-second and -first order kinetics models, for triclosan and caffeine, respectively. The promising results obtained open the possibility of using the synthesized nanomaterials for removing a variety of toxic and recalcitrant pollutants.